2015
DOI: 10.1556/066.2015.44.0031
|View full text |Cite
|
Sign up to set email alerts
|

Effect of shelf conditions on the phenolic fraction and oxidation indices of monovarietal extra virgin olive oil from cv. ‘Taggiasca’

Abstract: The quality of monovarietal extra virgin olive oil from cv. 'Taggiasca' is infl uenced by many factors that have impact on shelf-life as well as on sensory and healthy properties of the product. The aim of the work was to recreate the conditions similar to those in consumer sales point (conditions of "shelf"), maintaining the olive oil packaged in dark-green bottles at room temperature (between 18 and 25 °C) under artifi cial light and away from heat sources, monitoring the oils up to 12 months from bottling w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…Thus, it is necessary to take care not only of agronomical practices, raw material, harvesting, fruit storage and extraction technology, but also of each factor, which can affect its commercial life. In particular, oxygen, light and temperature are responsible for increasing deteriorative processes in EVOO as a consequence of oxidative and hydrolytic reactions ( Lanza et al., 2014 ). Shelf-life of EVOO has been assessed to be 12–18 months ( Cicerale et al., 2013 ), even if it has been shown that when it is properly stored in well-sealed packages, EVOO can reach the second year of storage maintaining its sensorial properties unaltered ( Piscopo and Poiana, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is necessary to take care not only of agronomical practices, raw material, harvesting, fruit storage and extraction technology, but also of each factor, which can affect its commercial life. In particular, oxygen, light and temperature are responsible for increasing deteriorative processes in EVOO as a consequence of oxidative and hydrolytic reactions ( Lanza et al., 2014 ). Shelf-life of EVOO has been assessed to be 12–18 months ( Cicerale et al., 2013 ), even if it has been shown that when it is properly stored in well-sealed packages, EVOO can reach the second year of storage maintaining its sensorial properties unaltered ( Piscopo and Poiana, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Packaging can directly influence olive oil quality by protecting the product from two of the main factors inducing oxidative deterioration: oxygen and light ( Lanza et al., 2014 ). Moreover, it is essential to avoid the contact with inadequate materials such as metal containers which can initiate oxidative degradative reactions ( Sgherri et al., 2018 ), thus affecting the shelf-life of the oil.…”
Section: Introductionmentioning
confidence: 99%
“…As for other foods that are produced over a limited period of time but are consumed throughout the year, EVOOs need to be stored. The storage and packaging conditions can have a significant influence on the commercial life of EVOOs, according to the type of packaging material and the external environmental conditions (e.g., darkness, diffuse artificial light, direct sunlight, temperature, air exposure) (Abbadi et al, ; Angerosa, Di Giacinto, & De Mattia, ; Caponio, Bilancia, Pasqualone, Sikorska, & Gomes, ; Kanavouras & Coutelieris, ; Lanza, Di Serio, Giansante, Di Loreto, & Di Giacinto, ; Pristouri, Badeka, & Kontominas, ; Tan, Che Man, Selamat, & Yusoff, ). Suitable storage conditions are, thus, of great importance to maintain the high quality of EVOOs.…”
Section: Introductionmentioning
confidence: 99%
“…It begins with the ripening of the olive and finishes with the packaging. The latter is a very important aspect, because several factors, such as the oxygen availability, as well as temperature and light during storage, can affect the EVOO shelf-life [10].…”
Section: Introductionmentioning
confidence: 99%
“…EVOO quality may also be directly influenced by the primary storage containers, as well as by the final packaging [10]. Indeed, contact with inadequate materials contribute oxidative degradation reactions [21].…”
Section: Introductionmentioning
confidence: 99%